Hidup Di Tepi Garis Pertempuran: Kondisi Sosial Rakyat Kebumen 1947-1948 - Zazid Hisyam, Nur (Siginjai: Jurnal Sejarah, 2024)
The period of physical revolution in Indonesia was a difficult time for the people of Kebumen. During that time, many social changes occurred which put pressure on people's lives. The previously calm social life for lower-class people suddenly had to change. People are faced with feelings of anxiety and fear of violence that suddenly appear. Since its arrival in Indonesia, the Dutch army carried out its military aggression which was the beginning of this disaster. For the people of Kebumen, the occupation of part of the Kebumen region by the Dutch army with the use of Gombong as their base as well as the demerger line between Dutch and Indonesian rule made the people's conditions increasingly difficult. This article focuses on the social conditions of the people of Kebumen during the revolutionary period which describes the difficulties faced by the people because of the violence they often experienced in the form of arrests, torture and shootings. The historical method is the basis for the explanation of this article, accompanied by credible historical sources. The sources used in this paper include primary sources in the form of archives from ANRI, archives of the Indonesian republican police, archives of the Indonesian delegation, archives of the state secretariat, archives of the ministry of defense and archives of the ministry of information.